A conceptual critique of Prevent: Can Prevent be saved? No, but…. (August 2020) - Skoczylis, Joshua; Andrews, Sam
The UK's Prevent policy continues to fail in its fundamental purpose to prevent extremism and has at times even created spaces where extremism flourishes. This article goes beyond the mechanism of implementation providing a conceptual understanding of how Prevent maintains the neoliberal status quo. The promotion of the neoliberal status quo, depoliticisation and a lack of focus on root causes continue to undermine Prevent. Any policy aimed at preventing extremism and terrorism must be well integrated into the government's wider social policies, shifting away from securitisation and towards improving society. Reducing extremism becomes a by-product of a much broader attempt at changing society, focusing on policies that address racism, gender and socio-economic inequality. These policies, we argue, must encourage political engagement with all groups, especially marginalised ones. Creating a healthier democracy will reduce risks of extremism and will negate the need for a Prevent policy based on discrimination and securitisation.